(3fhQ GdSLjI aj Md CdaGX GdCLQhejIs - (3GdTQHjfj GdeUQj GdTGaYj, TeS GdOjf (B- (3GdNWjH, eMeO Hf CMeO, J (B977 (3g`s ((3Ydj Hf YHO GdgGOj GdTGaYjs)
(3ChdgG (B:s
(3GdMeO ddg QGaY GdefJLjfajbhd eMeO GdTQHjfj GdNWjH Ef ebOeI GdTjN eMeO Hf YHO Gddg Hf OGhhO GdUfgGLj GdTgjQ HGdBLQhej deG cGfJ ef CMSf eNJUQ aj Yde GdYQHjI SCdfj HYV CUMGHfG Cf CVY Ydjg TQMGhSejJg fhQ GdSLjI aj Md CdaGX GdCLQhejIs
(3BNQgG (B:s
(3hEfeG jaJQb Mce GdeLGR hGdMbjbI GdXGgQjf GdeVeQjf ceG bGdg GHf gTGe aj eZfjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 69s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs